The adoption and implementation of the food quality system (HACCP) in Mediterranean Region of Turkey - Mutlu S.; Bal T.; Say D.; Emeksiz F. (The market for organic products in the Mediterranean region, 2003)
Food quality has become a considerable issue in food sector over the past decade. Since the food safety concepts has been paid attention in the developed countries. It is obviously clear that keeping the competition power can be provided by the way of producing quality products. In the developing countries, food quality problems may prevent international trade because of increasing food quality regulations. The aim of this study is to determine the problems which the firms in the Mediterranean region in Turkey faced with as applying HACCP, to examine the expenses of the HACCP implementation in food firms, to determine the economic and social advantage of HACCP and conscious level of the firms about HACCP. The firms applying HACCP tend to export to the EU countries; employ more qualified personnel; and in these firms the managers are not generally the owner of the companies. The most important cost category consists of building, ground and the arrangement of the surroundings. This cost category is occurred because that the HACCP system requiring rearrangement or establishment of this firms. The most important problem as establishing and applying HACCP system is deficiency of training about HACCP.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)